2023
DOI: 10.1111/nmo.14528
|View full text |Cite
|
Sign up to set email alerts
|

Novel sensory trigger for gastrocolonic response

Abstract: The gastrocolonic response (GCR), often referred to as gastrocolonic reflex, describes a physiologic increase in motor activity of the colon following meal ingestion, which was first described by Cannon in 1902, with the term GCR being proposed by Hertz a few years later. 1,2 The increase in colonic motor activity from baseline maybe subtle or more pronounced, mostly in younger children, resulting in high amplitude propagated contractions (HAPC). 3 The response propagates fecal content and gas throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…However, in specific cases of pan‐colonic dysmotility, limited left CM reflected motility of the entire colon, such as in cases of colonic hyperactivity and in cases of abnormal gastrocolonic response. These conditions apparently seem to affect the entire colon but can be identified through a segmental analysis, as was previously demonstrated 18 . Suggested protocol for evaluation of left CM in pediatric patients, based on our study results, is presented in Figure 5.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, in specific cases of pan‐colonic dysmotility, limited left CM reflected motility of the entire colon, such as in cases of colonic hyperactivity and in cases of abnormal gastrocolonic response. These conditions apparently seem to affect the entire colon but can be identified through a segmental analysis, as was previously demonstrated 18 . Suggested protocol for evaluation of left CM in pediatric patients, based on our study results, is presented in Figure 5.…”
Section: Discussionsupporting
confidence: 53%
“…These conditions apparently seem to affect the entire colon but can be identified through a segmental analysis, as was previously demonstrated. 18 Suggested protocol for evaluation of left CM in pediatric patients, based on our study results, is presented in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research, using intraluminal EEnG measurements, has shown that children suffering from HSCR exhibited no slow wave colonic activity as opposed to healthy controls, in whom slow wave colonic activity was present 14 . Additionally, Dorfman et al documented an increase in colonic activity upon meal intake in children using colonic manometry recordings 15 . Our contradicting results may be explained by the fact that newborns and young children were not capable to lie completely still during both 20-minte sEEnG recordings.…”
Section: Discussionmentioning
confidence: 99%